2014
DOI: 10.30955/gnj.001234
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between rainfall and run-off In the Stratoni Region (N. Greece) after the storm of 10th February 2010

Abstract: Extreme floods often demonstrate unanticipated characteristics that pose problems for management and response. The flood in the Stratoni region in February 2010 provided an example of such unexpected response. The aim of this paper is the quantification of the hydrologic response of the torrents that outfall in the area of Stratoni of the prefecture of Chalkidiki by means of the synthetic unit hydrograph method. For this purpose, the effective rainfall is estimated with a Curve Number of Soil Conservation Serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…Therefore, AMC is of higher importance than the forested area, because during extreme rainfall events the forest soil water retention capacity decreasing rapidly (Hegg, 2006;Schleppi, 2011). Recent studies in the study area indicate that Chalkidiki region is extremely vulnerable to flash floods, despite the considerable percent of forested area (Kastridis & Stathis, 2012;Kastridis & Stathis, 2017;Kastridis & Stathis, 2020;Sapountzis & Stathis, 2014;Stathis & Stefanidis, 2001;Stefanidis et al, 2007).…”
Section: The Mechanism Of Flash Flood Eventgeomorphologic Configuration -Ground and Aerial Observationsmentioning
confidence: 94%
See 4 more Smart Citations
“…Therefore, AMC is of higher importance than the forested area, because during extreme rainfall events the forest soil water retention capacity decreasing rapidly (Hegg, 2006;Schleppi, 2011). Recent studies in the study area indicate that Chalkidiki region is extremely vulnerable to flash floods, despite the considerable percent of forested area (Kastridis & Stathis, 2012;Kastridis & Stathis, 2017;Kastridis & Stathis, 2020;Sapountzis & Stathis, 2014;Stathis & Stefanidis, 2001;Stefanidis et al, 2007).…”
Section: The Mechanism Of Flash Flood Eventgeomorphologic Configuration -Ground and Aerial Observationsmentioning
confidence: 94%
“…nerable to flash floods, despite the considerable percent of forested area(Kastridis & Stathis, 2012;Kastridis & Stathis, 2017;Kastridis & Stathis, 2020;Sapountzis & Stathis, 2014;Stathis & Stefanidis, 2001;Stefanidis et al, 2007).Concerning the urban sprawl, the comparison between the orthoimages of the study area dated back to 1945 and the recent orthoimages from 2007, showed that Olympiada settlement has been expanded on the floodplain of Mpasdekis main stream (Figure 2). It is evident that the alluvial fans of the floodplain were active back to 1945, the north part of Olympiada was built on the deltaic depositions of Mpasdekis stream and the riparian forest was clear cut.…”
mentioning
confidence: 90%
See 3 more Smart Citations